A web-application vulnerability detection model - V. V. Bakhtizin; D. E. Onoshko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A web-application vulnerability detection model based on static analysis of source codes is proposed. Evaluation system used by the vulnerability detection model is described. Several ways of extending the model for certain difficult cases are shown.